Fertility and family labor supply - Jakobsen, KM; Jørgensen, TH; Low, H (University of Oxford, 2022)
We study how fertility decisions interact with labor supply of men and women. First, we use longitudinal Danish register data and tax reforms to show that increases in wages of women decrease fertility while increases in wages of men increase fertility. Second, we estimate a life-cycle model to quantify the importance of fertility adjustments for labor supply and long-run gender inequality. Wage elasticities of women are more than 10% lower if fertility cannot be adjusted in our model. Finally, we show that human capital depreciation around childbirth is an important driver of the long-run gender wage gap.